The exploitation of obsidian in the Central Plateau of Santa Cruz, Argentina: Results from La María and Cerro Tres Tetas and a regional perspective : La explotación de la obsidiana en la Meseta Central de Santa Cruz, Argentina. Resultados de La María y Cerro Tres Tetas en perspectiva regional - Cueto, Manuel Enrique (2016)
La María and Cerro Tres Tetas archaeological localities are located in the Central Plateau, in the province of Santa Cruz, Argentine Patagonia. This area presents abundant lithic raw materials of very good quality for knapping including flint, chalcedony and silicified wood. These raw materials were used by the inhabitants of the region since the end of the Pleistocene until recent historical times. Besides, we have recorded the exploitation of exotic stones in low proportions at the archaeological sites. Among these, the most abundant is obsidian which probably comes from sources located more than 125 km away. In this context, the use of this type of raw material should be evaluated in terms of social and symbolic issues. In this paper, we examine the strategies of acquisition and reduction of the obsidian found at the archaeological sites Cerro Tres Tetas 1, Casa del Minero 1, Cueva de La Ventana, La Mesada and Cueva Túnel. We carry out a technomorphological analysis of the obsidian remains from these sites. Results from this work strengthen the idea that the groups which lived in the Central Plateau knew about and exploited an obsidian source known as Pampa del Asador. A raise in the use of this raw material throughout time is recorded, reaching its peak in the late Holocene. We identified two different moments in the exploitation of obsidian at the regional level. During the final Pleistocene and early Holocene, obsidian would not have played a relevant role in the organization of technology. Production sequences indicate that tools probably were entered to the sites already manufactured. During the middle and late Holocene nodules and cores could have been brought into the sites. The strategies involved in their reduction are in broad terms similar to those implemented with local raw materials; there is no evidence that obsidian had more value in any way. On the other hand, it is also not possible to state that there was just an eventual exploitation of this raw material. We believe that obsidian was acquired during mobility circuits which enabled the contact between different groups.